Psychometric Properties of a New Questionnaire Assessing the Mothers’ Knowledge and Perception About the Oral Health of Their School Children - Zahra Momeni; Katayoun Sargeran; Reza Yazdani; Shirin Shahbazi Sighaldeh (Frontiers in Dentistry, 2022)
Objectives: The aim of the present study was to develop and evaluate the psychometric properties of an instrument in Persian to assess the mothers’ knowledge, and perception about oral health of school children.